Considerable doubt about rubella screening and vaccination among unvaccinated orthodox protestant women: a mixed-methods study - Anne C. de Munter; Jeannine L. A. Hautvast; Wilhelmina L. M. Ruijs; Robert A. C. Ruiter; Marlies E. J. L. Hulscher (BMC, 2023)
Abstract Background Women who are susceptible to rubella are advised to vaccinate against rubella to prevent infection in future pregnancies, and thus avert the risk of congenital rubella syndrome in their unborn child. Rubella outbreaks periodically occur in the under-vaccinated orthodox Protestant community in the Netherlands. The objective of this mixed-methods study was to determine and understand personal experience with rubella, perceived rubella susceptibility, and intention to accept rubella screening and vaccination among unvaccinated orthodox Protestant women. The ultimate aim of this study was to inform policy and practice and contribute to the prevention of cases of congenital rubella syndrome. Methods A mixed-methods study was conducted combining an online survey and semi-structured interviews among unvaccinated Dutch orthodox Protestant women aged 18-40 years. Descriptive analysis was used for quantitative data. Qualitative data was analysed using codes and categories. Results Results of the survey (167 participants) showed that most participants had personal experience with rubella (74%, 123/167) and 101 women (61%, 101/167) indicated they had had rubella themselves. More than half of the women were undecided whether to accept rubella susceptibility screening (56%; 87/156) or rubella vaccination (55%; 80/146). Qualitative findings (10 participants) showed that most women thought they were not susceptible to rubella. Indecisiveness and negative attitudes to accept rubella vaccination were related with religious arguments to object vaccination and with women's perception of absence of imminent threat of rubella. Furthermore, results showed presence of misconceptions among women in the interpretation of their susceptibility and high confidence in their parents' memory that they had experienced rubella as a child although no laboratory screening had been conducted. Conclusions In light of an imminent rubella outbreak in the Netherlands, a tailored education campaign should be prepared aimed at and established in cooperation with the under-vaccinated orthodox Protestant community. Health care providers should provide adequate information on rubella and support decision-making in order to stimulate women to make a deliberate and informed decision on rubella screening and, if necessary, subsequent vaccination.